Abstracts - Presenters at the York University Undergraduate Research Fair, 2021, (Revue YOUR Review (York Online Undergraduate Research), 2022)
The following abstracts accompanied posters presented at the ninth annual multidisciplinary Undergraduate Research Fair held at York University (Toronto, Canada) in March 2021. The poster images can be viewed by clicking on “Poster PDF” under each abstract title in the “Abstracts & Posters” section on the Revue YOUR Review website: https://yourreview.journals.yorku.ca/index.php/yourreview/issue/view/2218